Beyond the supply side: Use and impact of municipal open data in the U.S. (May 2021) - Wilson, Bev; Cong, Cong
Highlights: Impact of open government data has been primarily within local government itself. Lack of monitoring mechanisms makes it difficult to evaluate their broader effects. Some respondents question emphasis on individual residents as users of OGD. OGD initiatives should be integrated with digital equity efforts to achieve goals. Abstract: While the number of open government data initiatives has increased considerably over the past decade, the impact of these initiatives remains uncertain. Recent studies have been critical of the "bias toward the supply side" and lack of "sufficient attention to the user perspective" in the way that open government data initiatives are implemented. This article asks: (1) who is using municipal open government data resources and for what purposes? and (2) what impact are municipal open government data having in cities where they have been implemented? We performed a qualitative analysis of 26 semi-structured telephone interviews conducted with government staff, civic technologists, and private sector stakeholders in nine cities around the United States. Each of these 30 to 45-minute telephone interviews were transcribed and analyzed to distill insights regarding the use and impact of municipal open government data in the nine cities considered. We find that the array of actors within open government data ecosystems at the local level is expanding as distinctions between the public and private sectors becomes increasingly blurred and that the demands of managing and sustaining these initiatives has led to changes in the services offered by local government, as well as in the duties of government staff. The impact of these data resources has been primarily felt within local government itself, although the lack of monitoring mechanisms makes it difficult to systematically evaluate their broader effects. We conclude that open government data initiatives should be coordinated and better integrated with digital equity and digital inclusion efforts in order to advance their political and social goals.